2021
DOI: 10.3802/jgo.2021.32.e85
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy utilization rate and effect on survival in cervical cancer patients in Korea

Abstract: Objective External beam radiation therapy (EBRT) with concurrent chemotherapy followed by intracavitary brachytherapy is the standard treatment in locally advanced cervical cancer. This study examined the brachytherapy utilization rate and evaluated the effect of brachytherapy on survival in cervical cancer patients in Korea. Methods In this study, data from the Korea Central Cancer Registry and Korean National Health Insurance Service and data on mortality from Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
0
0
1
Order By: Relevance
“…Locally advanced/advanced stage was also a mild risk factor for metastatic recurrence in the mixture cure model. Consistent with our study, a number of studies have confirmed that FIGO has a strong association with metastatic recurrence [7][8][9]. The FIGO 2018 staging system reflects patient prognosis, as Qin noted [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Locally advanced/advanced stage was also a mild risk factor for metastatic recurrence in the mixture cure model. Consistent with our study, a number of studies have confirmed that FIGO has a strong association with metastatic recurrence [7][8][9]. The FIGO 2018 staging system reflects patient prognosis, as Qin noted [29].…”
Section: Discussionsupporting
confidence: 91%
“…There is well-documented evidence which bears a significant influence on prognoses, such as the FIGO stage [8,9] and concurrent chemotherapy [6,10]. However, some controversies remain to be solved; for instance, some studies reported inconsistent results for age [11,12] and differentiation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of brachytherapy include the delivery of a high dose of radiation due to the proximity of the equipment to the treatment area and the minimization of effects on normal tissues in the bladder and rectum [ 7 , 8 ] ( Figure 2 ). Data reported in 2021, however, showed that the availability of brachytherapy decreased from 84% in 2005 to 78% in 2013 in Korea and the number of medical institutions that offer brachytherapy also declined from 65% in 2006 to 36.8% in 2014 [ 9 ]. Since it is impossible to maintain facilities for brachytherapy available due to low medical reimbursements and challenges in equipment management, patients are often referred to other institutions.…”
Section: Latest Trends In Radiotherapymentioning
confidence: 99%
“…A braquiterapia de alta taxa dose, contexto deste estudo, é recomendada para casos de câncer ginecológico com estadiamento avançado, pois permite a aplicação de maior dose de radiação em curta distância e contribui para ampliar a sobrevida das mulheres com câncer ginecológico (Chargari et al, 2019;Kim et al, 2021). Apesar de sua ação benéfica no controle da doença, os efeitos adversos são inevitáveis.…”
Section: Introductionunclassified